EKRANISASI NOVEL MASIH ADA KERETA YANG AKAN LEWAT KARYA MIRA W. KE FILM ARINI MASIH ADA KERETA YANG AKAN LEWAT KARYA ISMAIL BASBETH - Melda, Rizka; Hudiyono, Yusak; Dahlan, Dahri (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This study focused on the form of ekranization, from the novel Masih Ada Kereta Yang Akan Lewat by Mira. W, and film Arini Masih Ada Kereta Yang Akan Lewat by Ismail Basbeth. The purpose of this study is to describe the form of ekranization (additions, changes, and shrinking) through a comparison of facts from the novel to the film. This research uses literature review study, with descriptive-qualitative method. The data of this research are words, phrases, and sentences that exist in the novel and film. The technique of collecting the data of this research namely reading, taking notes, describing the film into a script, translating the film script and clarify the data. The analytical technique used are data reduction, data display, and conclusion drawing or verification. This research used comparative literature theory, story facts (plot, setting, and character), ekranization (additions, changes, and shrinking). The result of this research showed that the comparison between Masih Ada Kereta Yang Akan Lewat novel by Mira. W and Arini Masih Ada Kereta Yang Akan Lewat film by Ismail Basbeth have similar story and used mix plot. The difference occurred in the emergence of plot and new setting in the film. It is happen because of the compaction of the story in the film, all the information contained in the novel cannot be added into the film. The form of ekranization (changes) that happened in the Masih Ada Kereta Yang Akan Lewat novel to the Arini Masih Ada Kereta Yang Akan Lewat, tentd to be more additions to the film such as the emergence of new setting and plot in the film. This is happen because of the past setting did not much brought up and there also an element of adult story in this film. And did not rule out the possibility, that every processes of ekranization must undergo a change.